2018
DOI: 10.1002/ejic.201800123
|View full text |Cite
|
Sign up to set email alerts
|

Increased Efficiency of Dye‐Sensitized Solar Cells by Incorporation of a π Spacer in Donor–Acceptor Zinc Porphyrins Bearing Cyanoacrylic Acid as an Anchoring Group

Abstract: Two novel porphyrins, ZnP(SP)CNCOOH and ZnPCNCOOH, bearing cyanoacrylic acid as an anchoring group were synthesized. Porphyrin ZnP(SP)CNCOOH contains a π-conjugated spacer (SP) for improved electronic communication between the dye and the TiO 2 electrode. The spacer bears polyethylene glycol chains to prevent dye aggregation and to enhance solubility of the dye. Electrochemical measurements and theoretical calculations suggest that both porphyrins are promising sensitizers for dye-sensitized solar cells (DSSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…In other papers (Liang et al, 2015; Panagiotakis et al, 2018) a remarkable broadening and a red-shift of the electronic absorption bands of ZnII porphyrins is reported after chemisorption on TiO 2 , with an enhanced light harvesting in the NIR range of wavelengths. Red-shifting of thee Q bands is also evident in the porphyrin 13 , endowed with DTE unit in β-position, upon being adsorbed on TiO 2 photoanode (Di Carlo et al, 2017).…”
Section: A4 β-Pyrrolic Substituted Znii Porphyrins As Light Harvestersmentioning
confidence: 83%
“…In other papers (Liang et al, 2015; Panagiotakis et al, 2018) a remarkable broadening and a red-shift of the electronic absorption bands of ZnII porphyrins is reported after chemisorption on TiO 2 , with an enhanced light harvesting in the NIR range of wavelengths. Red-shifting of thee Q bands is also evident in the porphyrin 13 , endowed with DTE unit in β-position, upon being adsorbed on TiO 2 photoanode (Di Carlo et al, 2017).…”
Section: A4 β-Pyrrolic Substituted Znii Porphyrins As Light Harvestersmentioning
confidence: 83%
“…As seen with the porphyrazine example, macrocycle-based push-pull chromophores such as phthalocyanines [89-91] (Figure 7) and porphyrins [92][93][94] are good candidates for use as organic dyes within DSSCs and have been extensively studied during the last decades. [105] have reported increased efficiency, with PCE ranging from 5 to 7.6%, using carefully designed zinc porphyrin pushpull derivatives grafted via cyanoacrylic acid on TiO2. Particularly, they showed, using a π-conjugated spacer between the chromophore and the anchoring group, enhanced electron transfer and hindered undesirable aggregation on the TiO2 surface.…”
Section: Sams From Push-pull Chromophores For Dye-sensitized Solar Ce...mentioning
confidence: 99%
“…Cheema et al [106] have obtained near-infrared absorption by conjugating the porphyrin to indolizine as a planar strong electron donor, thus inducing π-π interactions such as head-to-tail dye aggregation (Figure 8). [105] have reported increased efficiency, with PCE ranging from 5 to 7.6%, using carefully designed zinc porphyrin pushpull derivatives grafted via cyanoacrylic acid on TiO 2 . Particularly, they showed, using a π-conjugated spacer between the chromophore and the anchoring group, enhanced electron transfer and hindered undesirable aggregation on the TiO 2 surface.…”
Section: Sams From Push-pull Chromophores For Dye-sensitized Solar Ce...mentioning
confidence: 99%
“…However, the experiments confirmed that the presence of a dipole in the spacer did not change the electronic properties of the porphyrin ring. On the other hand, Panagiotakis et al prepared analogous donor–acceptor Zn porphyrins differentiated solely on the incorporation of a π-spacer between the porphyrin core and the cyanoacrylic-acid-anchoring group ( Figure 21 ) [ 91 ]. Both dyes showed favorable HOMO and LUMO electronic distributions and energy levels, as well as similar absorption spectra.…”
Section: Porphyrin Architectural Motifsmentioning
confidence: 99%